2010
DOI: 10.1002/14651858.cd007729.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Singing for children and adults with bronchiectasis

Abstract: Background Bronchiectasis is a common respiratory disease, especially in developing countries. Its cause varies from chronic infection to rare immune deficiencies. Bronchiectasis can be present with other respiratory diseases, such as chronic obstructive pulmonary disease (COPD). People with bronchiectasis may suffer from chronic cough, fatigue, shortness of breath, chest pain and coughing up blood. Their lung function may decline with time. These can also have a negative impact on their quality of life. Thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…There was no evidence for three studies (ie, dyslexia,30 cystic fibrosis,34 and bronchiectasis35) because they were not RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no evidence for three studies (ie, dyslexia,30 cystic fibrosis,34 and bronchiectasis35) because they were not RCTs.…”
Section: Resultsmentioning
confidence: 99%
“…MT is expected to improve gait and related activities such as rehabilitation in diseases of the central nervous system. There were also several studies that identified “Diseases of the respiratory system (J00-99).”22,35 Improvements seen in these studies were mainly due to effects of singing on breathing function, such as respiratory rate, and on the circulation function, such as heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…A Cochrane review, Singing for children and adults with bronchiectasis, found no eligible trials, therefore, no data were available for analysis. 261 A review 262 and a controlled study 263 around vitamin D both concluded that vitamin D deficiency was common in bronchiectasis, however, there were no RCTs assessing vitamin D. A case control study on a small number of patients (n=34 with bronchiectasis, n=29 without) found that the patients with bronchiectasis had significantly lower serum zinc level than the control group, however, there were no trials to evaluate the prophylactic or therapeutic use of zinc supplements. 264 …”
Section: Sectionmentioning
confidence: 99%
“…Singing can be performed individually or in a group (choir), and can be arranged or improvised. Singing is a much more complex physical activity than speaking due to the greater length of phrases and greater range of pitch required (Irons 2010). Singing is dependent on the use of the lungs for air supply.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, singing needs to be performed for a sufficient duration, and most likely at a sufficient intensity in order to ensure an effective stimulus for learning this technique and for potentially having an effect on important health outcomes. The precise ’dosage’ will likely vary for each person and may depend on their age, disease severity, and previous experience with singing (Irons 2010). …”
Section: Introductionmentioning
confidence: 99%